Congruence Between Methods for Identifying “Exceptional Physical Aptitude” in School Children - Sturza Milić, Nataša (Revija za elementarno izobraževanje, 2016)
The aim of this paper was to research the compatibility among various techniques (motor testing and teacher identification) for the identification of exceptional physical aptitude in students. The study was conducted on a sample of 503 children (241 girls and 262 boys) aged 10 – 10.5 and 25 teachers. It was confirmed that there was a statistically significant low correlation between the technique of motor testing and that of teacher identification (for girls r = 0.41; p < 0.01 and for boys r = 0.43; p < 0.01). Through a precise analysis of the subsamples of boys and girls identified through motor testing and teacher recognition, it was noted that the teachers successfully recognized 23 boys with high physical aptitude (54.8 %) and 17 girls with high physical aptitude (50 %). The results of this research can serve as a basis for a reliable identification of pupils with advanced physical aptitude and further work with them in the range of Physical Education and special school programs for the gifted in sport.
Keywords: identification; children with exceptional physical aptitude; teachers